2022
DOI: 10.1136/annrheumdis-2021-221824
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 mRNA COVID-19 vaccine and booster in patients with autoimmune rheumatic diseases: a national cohort study

Abstract: IntroductionEmerging evidence supports the immunogenic response to mRNA COVID-19 vaccine in patients with autoimmune rheumatic diseases (ARD). However, large-scale data about the association between vaccination, and COVID-19 outcomes in patients with ARD is limited.MethodsWe used data from Clalit Health Services, which covers more than half of the population in Israel. Patients with ARD older than 18 were included between 20 December 2021 and 30 September 2021, when the BNT162b2 mRNA COVID-19 vaccine, and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…The widest analysis so far performed is an Israeli national cohort study on 127,928 ASD patients reporting that people receiving mRNA COVID-19 vaccine and, particularly, the booster dose, had a better COVID-19 outcome. This finding might indirectly suggest an effective vaccine-driven immune protection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widest analysis so far performed is an Israeli national cohort study on 127,928 ASD patients reporting that people receiving mRNA COVID-19 vaccine and, particularly, the booster dose, had a better COVID-19 outcome. This finding might indirectly suggest an effective vaccine-driven immune protection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available literature showed that vaccination is the major tool to control and fight the COVID-19 pandemic; this is particularly true for frail patients’ populations [ 28 ] such as individuals with ASD. Several reports highlighted that ASD patients have a significantly higher prevalence of COVID-19 compared to general population [ 29 ] as well as that 3-dose vaccinated ASD subjects, compared to unvaccinated or 2-dose vaccinated patients, are more protected from severe COVID-19 consequences [ 30 ]. Nevertheless, even after the booster dose, a subgroup of ASD patients still maintains an impaired/absent humoral response, mainly (but not exclusively), due to concomitant DMT [ 5 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in India reported that post-vaccination antibody titers are the most important determinant for breakthrough infections [58]. On the other hand, many comorbidities were associated with breakthrough infections in Israel, but DM was not a significant factor [59].…”
Section: Immune Response To Infection and Vaccinationmentioning
confidence: 97%